Analisis Biaya Produksi Pelet Kayu (Cost Analysis of Wood Pellet Production) - Bintang CH Simangunsong; Karina A Wilma; EG Togu Manurung; Vera J Sitanggang; Armansyah H Tambunan (Jurnal Ilmu dan Teknologi Kayu Tropis, 2017)
Eco-friendly renewable energy such as wood pellet is necessary to replace fossil fuels. Hence, the wood pellet industry has been rapidly developed, particularly, in European and America countries. To capitalize a high demand of wood pellet in those countries, Indonesia’s wood pellet companies need analysis tools to make decision on management and operation of their wood pellet production such as productivity, efficiency, production cost and and profitability assessments. The objectives of this study were to analyze cost, break-event point and profitability of wood pellet production. This study was conducted at a large integrated wood based panel and wood working products company, which produces wood pellet from its forest products residues. The results showed that the production cost was about IDR 1.41 millions per ton or US$ 114 per ton. The break-even point was about 1400 tons per year or about 84.7% of actual production. The return on investment (ROI) was about 14.15 %, which was slightly higer than a lending rate of 10.25%.Key words: energy, production cost, profitability, wood pellet, wood residues